The Effectiveness of Sixth Grade Math in Focus Curriculum for Indonesian Christian Schools Students - Tia Aulia Putri Sadeva; Sylvia Primulawati; Robert Harry Soesanto; Evander Banjarnahor (South Sulawesi Education Development (SSED), 2025)
Math In Focus as a curriculum program is based on the Singaporean mathematics framework. However, it has been adjusted for U.S. classrooms by Great Source & Hougton Mifflin Harcourt publisher. This curriculum program was also used by a Christian school in Jakarta, Indonesia that has predominantly Indonesian students whose mother tongue was Indonesian language. Thus, the purpose of this study is to evaluate the effectiveness of Math In Focus curriculum program that was used in a Christian school in Jakarta, Indonesia, particularly in Grade VI. This research used a case study research methodology. The techniques of data collection used were questionnaire, interview, and observation. The results showed that the accuracy of the target was highly effective (81.5%), the aims of the program was also highly effective (82.5%), the socialization of the program was effective (71.5%), and the supervision of the program was also effective enough (70.5%). It can be concluded that Math In Focus curriculum program was effective enough (76.5%) for Indonesian Christian students in sixth grade although English is not their mother tongue. The other findings in this research were the supported and inhibited factors of the effectiveness.